Total Quality Management sebagai Model Peningkatan Mutu Berkelanjutan pada Lembaga Pendidikan Islam - Komaruddin Komaruddin; Safinah Safinah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to examine and formulate Total Quality Management (TQM) as a model for sustainable quality improvement in Islamic educational institutions through a value-based conceptual approach grounded in Islamic principles. Islamic educational institutions face increasingly complex quality challenges due to globalization, managerial professionalism demands, and growing public expectations for educational services. This research employs a qualitative approach using library research methods, analyzing books, scholarly journal articles, and relevant academic documents related to quality management and Islamic education. Data analysis was conducted through content analysis and thematic analysis to identify key principles, values, and implementation patterns of TQM within the context of Islamic education. The findings indicate that TQM serves as a strategic model capable of fostering systematic and continuous quality improvement when integrated with Islamic values such as ihsan, itqan, amanah, and istiqamah. The novelty of this study lies in the formulation of an Islamic education-based TQM model that positions value-based quality culture as the core of institutional management and interprets continuous improvement not merely as a technical process but also as a moral and spiritual commitment. This model contributes to the development of visionary leadership, participatory quality culture, and enhancement of both educational processes and outcomes.